Psychosocial and education programs for families with neurodegenerative diseases in Antioquia, Colombia: The Neuroscience Group of Antioquia social plan (2016)
Background: Since the inception of its Alzheimer's disease research program, the Neuroscience Group of Antioquia (GNA) has provided information, education, and social support for affected individuals, family caregivers, and other family members affected by Alzheimer’s disease and other neurodegenerative diseases. These diseases are associated with a range of personal and social challenges, which can affect the entire family. In order to address this problem, GNA, in collaboration with Genentech and Banner Alzheimer's Institute, has introduced Social Plan, consisting of programs to assist affected individuals and their families, provide coping strategies, support their participation in relevant research, and improve the quality of their lives. Methods: Health professionals have designed, implemented, refined, coordinated and overseen the program to help address the needs of patients, family caregivers, and other family members. Workshops on cognitive stimulation, painting, chorus, dance, crafts, support groups, care of the caregiver and meetings with young people to provide them support about the disease and their family environment, have been attended by affected persons and family members, many of whom are enrolled in the Colombian Alzheimer’s Prevention Initiative (API) Registry. The workshops are tailored to features and needs of the target population, such as the individuals’ age, place of residence and family role, and all services are provided whether or not individuals participate in any research studies. Results: The Social Plan has enrolled 760 people, including affected individuals, family caregivers and other immediate and more distant family members from the affected kindreds. Education around the disease and home patient care has been enhanced by the development of brochures, booklets and manuals designed by GNA to address particular needs and characteristics of the population. Conclusions: The Social Plan provides information, education, activities and support for families affected by Alzheimer’s disease and other neurodegenerative diseases of genetic origin. Participation in the Social Plan does not require patients and other family members to participate in the API Autosomal Dominant Alzheimer’s Disease Trial or other research studies. The Social Plan has underscored our commitment to both research and care, and advanced each of these important goals.